Energy modeling and photovoltaics integration as a mitigation measure for climate change impacts on energy demand - Dana I. Al Huneidi (18805828) (2022)
Due to Qatar’s increasing population and electricity consumption worldwide, several countries have started taking measures to reduce the carbon footprint associated with the growing energy demand. Furthermore, the climate in hot and humid countries like Qatar is becoming warmer over the years. This causes electricity consumption for cooling to increase, causing a rise in carbon emissions. Research is still being conducted on how renewable sources, along with other measures, can be optimally applied and how they can be integrated into building design to reduce energy consumption. Especially in Qatar, the application of renewable energy into buildings is more complex and limited. The purpose of this research is to test whether the application of demand-side management for a residential villa would efficiently reduce its annual energy consumption, hence reducing the environmental impact. This paper studies the energy demand of a residential villa case in Qatar for a reference year using Design Builder as an energy modeling software and proposes an optimum system for photovoltaics (PV) integration using HOMER software. The results show that PV integration on the villa rooftop reduces the energy demand and is found to be an economically and environmentally attractive solution. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.01.105